2016
DOI: 10.1186/s13570-016-0054-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of indigenous climate forecasting methods by the pastoralists of Northern Kenya

Abstract: This paper focused on the early warning signs of climate variation as indicated by the Borana community of Isiolo County, Kenya. The objective of the study was to determine the indigenous early warning signs used by the Borana to predict the onset of rainfall, floods and droughts and their efficacy. The study was guided by cultural ecological theory, and data was collected through secondary sources, semi-structured interviews, focus group discussions and direct observation. The findings revealed that the Boran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 2 publications
(1 reference statement)
1
21
0
Order By: Relevance
“…Findings from this study revealed the use of 'indigenous knowledge' by shine elders (these are lead elders with particular knowledge and responsibility in the community) and 'common sense' as frequent sources of climate information especially for pastoralists to forecast the onset of rainfall or prediction for a bad or a good year. Other studies in similar communities have also reported the use of 'indigenous knowledge' for predicting rains or droughts (Abate 2016;Kagunyu et al 2016;Egeru 2016). However, due to increasing climate variability and uncertainties, the traditional forecasting methods are perceived to be less reliable (Kagunyu et al 2016).…”
Section: Climate Change Informationmentioning
confidence: 97%
See 2 more Smart Citations
“…Findings from this study revealed the use of 'indigenous knowledge' by shine elders (these are lead elders with particular knowledge and responsibility in the community) and 'common sense' as frequent sources of climate information especially for pastoralists to forecast the onset of rainfall or prediction for a bad or a good year. Other studies in similar communities have also reported the use of 'indigenous knowledge' for predicting rains or droughts (Abate 2016;Kagunyu et al 2016;Egeru 2016). However, due to increasing climate variability and uncertainties, the traditional forecasting methods are perceived to be less reliable (Kagunyu et al 2016).…”
Section: Climate Change Informationmentioning
confidence: 97%
“…Other studies in similar communities have also reported the use of 'indigenous knowledge' for predicting rains or droughts (Abate 2016;Kagunyu et al 2016;Egeru 2016). However, due to increasing climate variability and uncertainties, the traditional forecasting methods are perceived to be less reliable (Kagunyu et al 2016). The modern/formal pathways represented by radio and television were not seen by participants as a reliable means for gaining climate information.…”
Section: Climate Change Informationmentioning
confidence: 97%
See 1 more Smart Citation
“…A4a, c). Kauffman and Cummings (1998), looking at three other pastures in Amazonia, found a range of 0.8-1.5 kgC m −2 of fine fuels, which included both live and dead leaf material as well as fine woody debris. Again, this corresponds well with our results (Fig.…”
Section: Appendix B: Grazing Intensity and Pasture Biomassmentioning
confidence: 99%
“…Climate change has and will continue to affect the timing, length, and quality of growing seasons (Porter et al, 2014); the associated impacts on planting and harvest date will affect the timing of crop residue burning, and people will shift the timing of burns to match the shifting phenology and how much to burn. Literature reviews and new research could shed light on indigenous methods for climate forecasting based on changes in the weather and vegetation (e.g., Kagunyu et al, 2016), as well as how these cues might be tied to the timing of prescribed fire for various purposes (e.g., Laris, 2002). Advanced analytical methods could also be applied to climate and fire history observations to look for lagged, region-specific relationships of agricultural burning with weather at weekly to 10 monthly time scales.…”
mentioning
confidence: 99%